To the plume moths fauna (Lepidoptera: Pterophoridae) of Laos - Ustjuzhanin, Peter Ya (Russian entomological journal)
Eight Pterophoridae species are reported for the fauna of Laos for the first time: Ochyrotica yanoi Arenberger, 1988, Bipunctiphorus dissipata (Yano, 1963), Lantanophaga pusillidactylus (Walker, 1864), Nippoptilia regulae (Meyrick, 1906), Tomotilus celebrates (Meyrick, 1932), Megalorhipida leucodactylus (Fabricius, 1794), M. subtilis (Rebel, 1907), Agdistopis sinhala (Fletcher, 1909).